Aplicação da técnica não destrutiva ultrassônica no controle de qualidade de ligas de alumínio envelhecidas artificialmente - Neves, Erick Cerqueira das (2019)
The microstructural control is an important tool for assure the integrity and the performance of parts made of Aluminum alloys. Although the conventional characterization techniques requires a large among of time to have some answers. As an alternative this study aims to make a correlation between Vickers hardness and ultrasonic parameters, targeting to have microstructural information for Al6351 alloys aged in different times. For this, the samples were submitted to different heat treatments cycles of solubilization, followed by artificial ageing treatment. Was evaluated the influence of precipitates density and morphology in the propagation of longitudinal ultrasonic waves, by the pulse eco UT technique. The results showed a relationship between the ultrasonic pulse characteristics and the aluminum alloy microstructural properties. This is the initial background to the development of nondestructive techniques for metallic alloys characterization.